Cancer patients and music: (prospective) results from a survey to evaluate potential complementary treatment approaches - Gencer, Deniz; Diel, Alina; Klotzbach, Katharina; Christians, Kathrin; Rauch, Matthias; Meissner, Rosa; Weiß, Christel; Hofmann, Wolf-Karsten; Hofheinz, Ralf-Dieter (Journal of cancer research and clinical oncology, 2019)
Many cancer patients (PTS) suffer from somatic or non-somatic symptoms. Studies have shown positive effects of music intervention (MI) on aspects of quality of life or symptom management.
Gesehen am 15.01.2020